Sex chromosome differentiation in Belostoma (Insecta: Heteroptera: Belostomatidae) - Bardella, V.B.; Dias, A.L.; Giuliano-Caetano, L.; Ribeiro, J.R.I.; da Rosa, R. (Genetics and molecular research, 2012)
Belostoma, a genus of the family Belostomatidae, includes species of great ecological importance as biocontrol agents. Few species of these species have been the subject of cytogenetic analyses. Karyotypic evolution in this genus involves agmatoploidy and simploidy; there are also different sex chromosome systems. We examined two Belostoma species (B. dilatatum and B. candidulum) collected from the Paranapanema River Basin (Brazil). Mitotic and meiotic analysis revealed 2n(♂) = 26 + X₁X₂X₃Y for B. dilatatum and 2n(♂) = 14 + XY for B. candidulum; both karyotypes have holokinetic chromosomes. Differences in heterochromatin distribution were also observed between the species, besides variation in the localization of CMA₃⁺/DAPI⁻ blocks. The existence of different types of sex chromosome systems in these species was confirmed based on arrangements of the chromosomes in different meiotic stages. We identified a new sex system in B. dilatatum, and make the first cytogenetic report on B. candidulum.